2006
DOI: 10.1302/0301-620x.88b10.17139
|View full text |Cite
|
Sign up to set email alerts
|

Systemic effects of severe trauma on the function and apoptosis of human skeletal cells

Abstract: Systemic factors are believed to be pivotal for the development of heterotopic ossification in severely-injured patients. In this study, cell cultures of putative target cells (human fibroblastic cells, osteoblastic cells (MG-63), and bone-marrow stromal cells (hBM)) were incubated with serum from ten consecutive polytraumatised patients taken from post-traumatic day 1 to day 21 and with serum from 12 healthy control subjects. The serum from the polytraumatised patients significantly stimulated the proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Patients with cerebral trauma are susceptible to HO, and systemic levels of basic fibroblast growth factor have been shown to be elevated in these instances. 40 Eid et al 41 found that serum from polytraumatised patients significantly inhibited apoptosis in human mesenchymal bone-marrow cells, further implicating a systemic factor in the enhancement of HO.…”
Section: Fig 3bmentioning
confidence: 99%
“…Patients with cerebral trauma are susceptible to HO, and systemic levels of basic fibroblast growth factor have been shown to be elevated in these instances. 40 Eid et al 41 found that serum from polytraumatised patients significantly inhibited apoptosis in human mesenchymal bone-marrow cells, further implicating a systemic factor in the enhancement of HO.…”
Section: Fig 3bmentioning
confidence: 99%
“…The increase in bone formation seen in NHO or fracture healing in patients with TBI confirmed the activation of osteogenic cells by osteogenic factors (40). In vitro evidence showed that osteogenic factors are in the systemic circulation (10,37,(41)(42)(43)(44). An association between callus formation and osteogenic factors in serum was also shown in vivo (41).…”
mentioning
confidence: 67%
“…Two studies investigating the osteogenic effect of CSF after TBI revealed that this fluid has osteogenic effect, namely, this effect has central origin (42,43). However, in these studies human tissues were rarely used and etiologic agents could not have been explained thoroughly (10,37,(41)(42)(43)(44).…”
mentioning
confidence: 99%
“…3,4 One study revealed that taking serum from polytraumatized patients and introducing it to osteoblasts and fibroblasts in vitro resulted in enhanced osteogenesis. 5 Heterotopic ossification may occur after trauma or surgery, but NHO is more prevalent in high-energy combat-related injuries of military service members. [6][7][8] Neurogenic HO is a common complication of trauma to the brain or spinal cord, and although the epidemiology is not fully understood, it can clearly be surmised that high-velocity neurotrauma greatly increases the likelihood of NHO.…”
Section: Introductionmentioning
confidence: 99%